2018
DOI: 10.1002/jbm.b.34299
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of mandibular bone defects using biphasic calcium phosphate bone substitutes with simultaneous implant placement in mini‐swine: A pilotin vivostudy

Abstract: This study aimed to investigate implant osseointegration using a new strategy of biphasic calcium phosphate (BCP) bone substitutes with simultaneous implant placement in mandibular reconstruction. Additionally, the temporal transcriptional profile associated with the early biological processes during osseointegration was determined. BCP and hydroxyapatite (HA) bone substitutes with simultaneous implant placement were grafted into mandibular defects created in mini-swine. Radiographic, histological, and biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Biomaterials commonly investigated in bone regeneration can be classified based on their source of origin, mainly natural and synthetic biomaterials ( Table 1 ). [ 22 ] Naturally occurring biomaterials include inorganic ceramics such as calcium phosphates [ 23–26 ] and hydroxyapatite (HA). [ 27–29 ] Organic polymers consist of proteins such as: collagen, [ 30–32 ] gelatin, [ 33 ] elastin, [ 34 ] silk, [ 35 ] fibrin, [ 36,37 ] and keratin.…”
Section: Requirements and Challengesmentioning
confidence: 99%
“…Biomaterials commonly investigated in bone regeneration can be classified based on their source of origin, mainly natural and synthetic biomaterials ( Table 1 ). [ 22 ] Naturally occurring biomaterials include inorganic ceramics such as calcium phosphates [ 23–26 ] and hydroxyapatite (HA). [ 27–29 ] Organic polymers consist of proteins such as: collagen, [ 30–32 ] gelatin, [ 33 ] elastin, [ 34 ] silk, [ 35 ] fibrin, [ 36,37 ] and keratin.…”
Section: Requirements and Challengesmentioning
confidence: 99%
“…In recent years, some studies have shown that the Wnt/β‐catenin signalling pathway mediates the osteogenesis of osteogenic lineage cells on the surface of many kinds of implants, which can enhance osseointegration. An early transcription analysis of osseointegration showed that osteogenesis‐related TGF‐β/BMP and Wnt signalling pathways were upregulated in the treatment group that used biphasic calcium phosphate (BCP) as bone substitute materials (Z. Zhang et al, 2019). Huang et al (2019) combined lithium with sandblasting, large‐grit and acid‐etching (SLA) of titanium implants through hydrothermal treatment and found that the implants could activate the Wnt/β‐catenin signalling pathway to promote bone formation and inhibit osteoclasts.…”
Section: Wnt and Implant Osseointegrationmentioning
confidence: 99%
“…Consequently, it is widely applied in the fields of bone defect repair and bone tissue regeneration. 16 Melatonin is a hormone secreted by the pineal gland in humans that regulates the sleep-wake cycle, inhibits tumor growth, acts as an antioxidant, and modulates the immune system. 17 Melatonin receptors have two subtypes, MT1 and MT2, which belong to the G protein-coupled receptor family.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is widely applied in the fields of bone defect repair and bone tissue regeneration. 16…”
Section: Introductionmentioning
confidence: 99%